In silico study of porphyrin-anthraquinone hybrids as CDK2 inhibitor. (April 2017) - Arba, Muhammad; Ihsan, Sunandar; Ramadhan, La Ode Ahmad Nur; Tjahjono, Daryono Hadi
Graphical abstract: mono-H2 PyP-AQ in the binding pocket of CDK2. Highlights: Porphyrin-anthraquinone hybrids were designed and evaluated for their CDK2 inhibitory activity. All porphyrin hybrids interacted with key residues in the ATP-binding site of CDK2. The predicted binding energy of mono-H2 PyP-AQ was about three times better than that of DTQ. Abstract: Cyclin-Dependent Kinases (CDKs) are known to play crucial roles in controlling cell cycle progression of eukaryotic cell and inhibition of their activity has long been considered as potential strategy in anti-cancer drug research. In the present work, a series of porphyrin-anthraquinone hybrids bearing meso -substituents, i.e. either pyridine or pyrazole rings were designed and computationally evaluated for their Cyclin Dependent Kinase-2 (CDK2) inhibitory activity using molecular docking, molecular dynamics simulation, and binding free energy calculation. The molecular docking simulation revealed that all six porphyrin hybrids were able to bind to ATP-binding site of CDK2 and interacted with key residues constituted the active cavity of CDK2, while molecular dynamics simulation indicated that all porphyrins bound to CDK2 were stable for 6 ns. The binding free energies predicted by MM-PBSA method showed that most compounds exhibited higher affinity than that of native ligand (4-anilinoquinazoline, DTQ) and the affinity of mono-H2 PyP-AQ was about three times better than that of DTQ, indicating its potential to be advanced as a new CDK2 inhibitor.